The Routledge handbook of sport and sustainable development - McCullough, Brian P.; Kellison, Timothy; Melton, E. Nicole (New York : Routledge, 2022)
"The Routledge Handbook of Sport and Sustainable Development is a comprehensive and powerful survey of the ways in which sport engages with its social, environmental, and ethical responsibilities. It considers how sport can use its unique profile and platform to influence the attitudes of sport fans and consumers to promote positive social and environmental action around the world, and to contribute to sustainable development, perhaps the most important issue of our time. The book is structured around the 17 UN Sustainable Development Goals, with a section devoted to each goal that contains chapters reviewing key theory and current research, measurement and evaluation issues, and the application of current knowledge in real-world development situations. Drawing on research and expertise from management, sociology, development studies, psychology, and other disciplines, the book examines the role that sport must play in areas such as health and well-being, poverty, education, gender equality, decent work, responsible consumption, and climate action. Representing a keynote work on the wider social responsibilities of sport as both an industry and sociocultural activity, this is essential reading for any advanced student or researcher working in sport development, sport management, sport sociology, event studies, development studies, or environmental studies, and for any development practitioner or sport management professional looking to understand how to achieve positive social change in and through sport"--
An Introduction to Sport and Sustainable Development / Brian P. McCullough, Timothy Kellison and E. Nicole Melton -- Part 1. Sustainable Development Goal 1: No Poverty -- Part 2. Sustainable Development Goal 2: Zero Hunger -- Part 3. Sustainable Development Goal 3: Good Health and Well-Being -- Part 4. Sustainable Development Goal 4: Quality Education -- Part 5. Sustainable Development Goal 5: Gender Equality -- Part 6. Sustainable Development Goal 6: Clean Water and Sanitation -- Part 7. Sustainable Development Goal 7: Affordable and Clean Energy -- Part 8. Sustainable Development Goal 8: Decent Work and Economic Growth -- Part 9. Sustainable Development Goal 9: Industry, Innovation, and Infrastructure -- Part 10. Sustainable Development Goal 10: Reduced Inequalities -- Part 11. Sustainable Development Goal 11: Sustainable Cities and Communities -- Part 12. Sustainable Development Goal 12: Responsible Consumption and Production -- Part 13. Sustainable Development Goal 13: Climate Action -- Part 14. Sustainable Development Goal 14: Life Below Water -- Part 15. Sustainable Development Goal 15: Life on Land -- Part 16. Sustainable Development Goal 16: Peace, Justice, and Strong Institutions -- Part 17. Sustainable Development Goal 17: Partnerships for the Goals.
Keywords: Sports -- Environmental aspects; Sports administration -- Environmental aspects; Sustainability; Sports facilities -- Environmental aspects; Sports -- Social aspects; SPORTS & RECREATION / Sociology of Sports